Amazing Grace - Hoffman, Mary (New York : Dial Books for Young Readers, 1991)
Although classmates say that she cannot play Peter Pan in the school play becuase she is black and a girl, Grace discovers that she can do anything she sets her ind to do.
Keywords: Afro-American-Fiction; Identity-Fiction; Theater-Fiction